Natural hydraulic lime (nhl3.5) mortars with scrap tire rubber - Faria, Paulina (2016)
The use of wastes and industrial by-products as building materials is an important issue in order to decrease costs with waste management and the embodied energy of building products. In this study scrap tire rubber was used as additional aggregate of mortars based on natural hydraulic lime NHL 3.5 and natural sand. Different particle size fractions and proportions of scrap tire rubber were used: a mix obtained directly from industry and separated fine, medium and coarse fractions; 0 %, 18 %, 36 % and 54 % of the weight of binder, corresponding to 2.5 %, 5 % and 7.5 % of the weight of sand. As mortars based on NHL specifications became stricter with the current version of EN 459–1:2015, the influence of the rubber’s additions on the mortars’ fresh state, mechanical and physical performance is presented in this work: flow table consistency, water retention, dynamic elasticity modulus, flexural and compressive strength, open porosity and bulk density, capillary absorption, drying and thermal conductivity are studied. The use of the rubber mix coming from the waste tire industry seems advantageous and may open possibilities for use as raw material by the mortars industry.